Quantification of microglial late reaction to stereotactic irradiation of the rat brain using computer-aided image analysis - Reinacher, Peter; Blum, Christoph; Gass, Peter; Karger, Christian; Debus, Jürgen (Experimental neurology, 2002)
The role of microglial cells in the late delayed reaction following radiotherapy of brain tumors has not been elucidated. To investigate the late delayed response of microglial cells to radiation, we stereotactically irradiated spherical treatment volumes in the right frontal lobe of rat brains. Doses of 20, 30, 40, and 50 Gy were used in combination with two different collimators. The response of microglial cells at 10 and 19 months after irradiation was determined with Anti-CD 11 b/c (Ox 42) as an immunohistochemical marker. For evaluation of immunostaining, we developed a method using computer-aided image analysis in which the ratio of the area of stained cells to that of nonstained brain tissue is calculated. In addition, quantification of Ox-42+ cells per microscopic field was performed. Animals treated with 30 Gy or more had significantly increased total areas of staining at both time points studied. In contrast, the number of stained cells at 10 months increased significantly only in animals treated with 30 or 40 Gy. Likewise, at 19 months, this number increased significantly only in animals treated with 40 Gy or more. These results indicate that computer-aided determination of the area of stained cells is more sensitive than the counting of stained cells. We have demonstrated that microglial cells respond to stereotactic irradiation in a dose-dependent fashion. The image analysis we employed for this purpose is a systematic method to evaluate immunohistochemical staining.